Does having children affect womens entrepreneurship decision Evidence from Nigeria - Ajefu, J. B. (SpringerLink, 2019)
This paper investigates the impact of fertility on women’s entrepreneurship decision in Nigeria, using the 2008 and 2013 cross-sectional Demographic Health Surveys data. In order to mitigate the potential endogeneity associated with fertility decision, the study explores an exogenous variation in family size using twin births in an instrumental variable (IV) analysis. Both the Ordinary Least Squares (OLS) and Two-Stage Least Squares (2SLS) estimate show that having children is positively associated with women’s entrepreneurship decision, and there are heterogeneous effects across the subsamples by women’s age. The results of this study are robust to using the number of children younger than age five in the home as an alternative definition of fertility.
Keywords: Children; Women; Entreprenuership; Nigeria